The Potential Renoprotective Effect of Fedratinib in Renal Ischemia Reperfusion Injury in Male Rat Model - Hussein, Furqan Hashim; Mosawi, Najah R. Al (South Eastern European Journal of Public Health, 2024)
Renal Ischemia Reperfusion Injury (RIRI) is a serious condition that arises following kidney transplantation or other circumstances that result in decreased blood supply to the kidneys, these conditions cause a harm to the renal tissue. Gaining insight into the fundamental mechanisms of RIRI, including inflammation, cell death pathways, is essential for the development of successful therapeutic approaches. Objective: This study aimed to assess the effects of Fedratinib, a JAK2 inhibitor, in reducing RIRI in a rat model. The study involved rats divided into four groups: Sham group, control group, vehicle group, and Fedratinib group. Rats underwent anaesthesia and midline incision to expose renal pedicles, with blood flow halted using microvascular clamps. The wound was stitched, and the animals were left for 90 minutes to allow reperfusion. Blood samples were collected from the heart apex to assess serum urea and creatinine, and renal slices were used for PCR to detect the jak2/stat3 pathway. The Elisa was used to evaluate TNF, IL-6, NF-κB, Bax, Bcl2, and HMGB levels. Results: IL-6 and TNF-α, and HMGB1 were identified to have a role in the development of RIRI, inhibition of JAK2/STAT3 pathway by Fedratinib significantly decrease their concentration and minimizing RIRI. Suppression of JAK2/STAT3 pathway led to a significant inhibition in NF-κB and apoptosis. Conclusion: Fedratinib has a potential preventive effect against RIRI through their activity as JAK2 inhibitor and inhibition of the following downstream inflammatory pathways.